Ms Nbwaa-ka-win: To cherish knowledge is to know wisdom - Kim English (York University Libraries, 2020)
This reflection paper represents my own efforts at personal reconciliation as a settler nurse educator. A portion of these efforts include my analysis and experience of the current state of nursing academia within the context of our profession's necessity to meet relevant calls to action stated within the Truth and Reconciliation Commission's report.   Key issues such as problematic texts accepted as 'nursing fundamentals', the invisibility of Indigenous knowledge coupled with the perpetuation of colonial stereotypes are discussed within the context of Nbwaa-ka-win. The application of post-colonial theory as part of a strengths-based approach to the decolonization of nursing education is presented.